Using the Finite Element Method to Simulate a Carbon Fiber Reinforced Polymer Pressure Vessel - I. R. Antipas; A. G. Dyachenko (Advanced Engineering Research, 2022)
Introduction. Over the past decade, global demand for pressure vessels has increased significantly, specifically in such industries as aviation, space, chemical, and oil and gas. Being under the constant impact of high internal pressure, the walls of the tanks are under increased stress, which can cause their sudden destruction. To eliminate this probability and improve the strength characteristics, the tanks are made in the form of metal cylinders with an internal coating of composite material consisting of resin reinforced with carbon fibers. This article aimed at studying the effect of the angle of inclination of carbon fiber on cylindrical tanks and determining the maximum destructive pressure using the finite element method of ANSYS program.Materials and Methods. Using the ANSYS program, a finite element model of a tank was created. It has a central part, which is a metal cylinder with an internal coating of composite material consisting of polymer reinforced with carbon fibers. At the ends of the tank, spiral wound hemispheres were placed. In these studies, SHELL 99 was used to model the layered composite material. The Tsai-Wu theory was used to determine the pressure tank failure criterion.Results. The cylindrical tank model was calculated for two types of fiber winding paths: annular and spiral, at different angles of their inclination. The results of the pressure value analysis for different fiber inclination angles showed that, starting from the angle value of 0° and up to 45°, it increased, and then, up to the angle value of 65°, it began to decrease. The critical pressure value for a carbon fiber reinforced tank was 207 MPa, which was obtained at a fiber angle of 45º.Discussion and Conclusion. Analysis of the studies showed that at a fiber inclination angle of 45º, the value of the maximum stress turned out to be the smallest, and the maximum possible destructive pressure at the same angle was 207 MPa. It follows, that the optimal fiber orientation angle to provide safe operation of the high-pressure tank is ± 45º, and the carbon fiber tank, calculated at the same fiber winding angle, has the maximum strength value.